2012
DOI: 10.1016/j.breast.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A first evaluation of breast radiological density assessment by QUANTRA software as compared to visual classification

Abstract: Breast radiological density is a determinant of breast cancer risk and of mammography sensitivity and may be used to personalize screening approach. We first analyzed the reproducibility of visual density assessment by eleven experienced radiologists classifying a set of 418 digital mammograms: reproducibility was satisfactory on a four (BI-RADS D1-2-3-4: weighted kappa = 0.694-0.844) and on a two grade (D1-2 vs D3-4: kappa = 0.620-0.851), but subjects classified as with dense breast would range between 25.1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 17 publications
7
110
0
Order By: Relevance
“…For example, considering the majority report in Phase 2, a cut-off value of 20.5% was observed. Even though Quantra studies have shown variable cut-off values, the differences in the majority of the studies are negligible (19.5-22%); 23,24,36 only one study has reported a lower cut-off value (13%). 25 Ciatto et al 23 have questioned this lower cut-off value, implicating differences in the radiologist panels as the cause for the lower value.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…For example, considering the majority report in Phase 2, a cut-off value of 20.5% was observed. Even though Quantra studies have shown variable cut-off values, the differences in the majority of the studies are negligible (19.5-22%); 23,24,36 only one study has reported a lower cut-off value (13%). 25 Ciatto et al 23 have questioned this lower cut-off value, implicating differences in the radiologist panels as the cause for the lower value.…”
Section: Discussionmentioning
confidence: 93%
“…Since BI-RADS depends on individual radiologist perception of MBD, 18,19,23 it is intuitive that an automated method such as Quantra, which is modelled with input from radiologists and selectively measures the volume of the dense tissue, may demonstrate greater reproducibility. However, this alone is not sufficient to warrant clinical implementation; automated measures must reflect the clinical opinion of the experienced breast radiologist consistently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Quantra has also been shown to accurately reproduce radiologists' BIRADS assessment on a two-category scale. 121,122 Volpara TM (Matakina Technology Limited) is also based on relative physics principles, and measures mammographic breast density by finding a reference point of entirely fat (P FAT ) in each image and then estimating X-ray attenuation relative to that point for all other points in the image. 123 Volpara calculates volume of dense tissue by integrating the thickness of dense tissue at each pixel level values over the image; it then computes the volume of the breast by multiplying the area of the breast by the recorded breast thickness.…”
Section: Categorisation Of Breast Composition Using "Quantitative Arementioning
confidence: 99%